2011
DOI: 10.1111/j.1466-7657.2011.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to HIV: a conflict situation for health workers

Abstract: KUMAKECH E., ACHORA S., BERGGREN V. & BAJUNIRWE F. (2011) Occupational exposure to HIV: a conflict situation for health workers. International Nursing Review58, 454–462 Aim:  To determine the frequency of occupational exposure to human immunodeficiency virus (HIV), the circumstances and predisposing factors, the high‐risk groups, the extent to which exposures are reported and the post‐exposure prophylaxis (PEP) utilized by health‐care workers (HCWs) and students in a Ugandan hospital. Background:  Occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
3
27
0
2
Order By: Relevance
“…The poorer practices of Ethiopian nurses when exposed to a potential infection risk may be attributable to lack of adequate risk perception and/or selective application of SPs. Several studies have documented selective application of SPs by healthcare providers (Gammon, Morgan‐Samuel, & Gould, ; Kumakech, Achora, Berggren, & Bajunirwe, ).…”
Section: Discussionmentioning
confidence: 99%
“…The poorer practices of Ethiopian nurses when exposed to a potential infection risk may be attributable to lack of adequate risk perception and/or selective application of SPs. Several studies have documented selective application of SPs by healthcare providers (Gammon, Morgan‐Samuel, & Gould, ; Kumakech, Achora, Berggren, & Bajunirwe, ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of training of HCW on prevention and management of occupational exposures and PEP among HCW has been described in resource-limited settings (Gupta et al, 2008;Kumakech et al, 2011). Lack of awareness could be addressed with appropriate and routine trainings on standard precautions, reporting and post-exposure care.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this recommendation, HCWs, and particularly nurses (Kumakech, Achora, Berggren, & Bajunirwe, 2011), often find it difficult to translate the principles of universal precautions into practice and may be noncompliant in their use (Aultman & Borges, 2011;Cutter & Jordan, 2004;Reda, Vandeweerd, Syre, & Egata, 2009). Several authors (Gammon et al, 2008;Kumakech et al, 2011) reported that practitioners were selective in the application of universal precautions and that compliance with infection control precautions was suboptimal. Studies have shown that nurse compliance with universal precautions is affected by the availability of protective equipment, the perceived commitment of management to safety, and perceptions that universal precautions interfere with job performance (Lee, 2009).…”
mentioning
confidence: 93%
“…Therefore, universal precautions have been recommended when caring for all patients, regardless of diagnosis (CDC, 1987). Despite this recommendation, HCWs, and particularly nurses (Kumakech, Achora, Berggren, & Bajunirwe, 2011), often find it difficult to translate the principles of universal precautions into practice and may be noncompliant in their use (Aultman & Borges, 2011;Cutter & Jordan, 2004;Reda, Vandeweerd, Syre, & Egata, 2009). Several authors (Gammon et al, 2008;Kumakech et al, 2011) reported that practitioners were selective in the application of universal precautions and that compliance with infection control precautions was suboptimal.…”
mentioning
confidence: 99%